Phenotypic Variation in a Four-Generation Family with Aniridia Carrying a Novel PAX6 Mutation - Grace M. Wang; Lev Prasov; Hayder Al-Hasani; Colin E. R. Marrs; Sahil Tolia; Laurel Wiinikka-Buesser; Julia E. Richards; Brenda L. Bohnsack (Journal of Ophthalmology)
Aniridia is a congenital disease that affects almost all eye structures and is primarily caused by loss-of-function mutations in the PAX6 gene. The degree of vision loss in aniridia varies and is dependent on the extent of foveal, iris, and optic nerve hypoplasia and the presence of glaucoma, cataracts, and corneal opacification. Here, we describe a 4-generation family in which 7 individuals across 2 generations carry a novel disease-causing frameshift mutation (NM_000280.4(PAX6):c.565TC>T) in PAX6. This mutation results in an early stop codon in exon 8, which is predicted to cause nonsense-mediated decay of the truncated mRNA and a functionally null PAX6 allele. Family members with aniridia showed differences in multiple eye phenotypes including iris and optic nerve hypoplasia, congenital and acquired corneal opacification, glaucoma, and strabismus. Visual acuity ranged from 20/100 to less than 20/800. Patients who required surgical intervention for glaucoma or corneal opacification had worse visual outcomes. Our results show that family members carrying a novel PAX6 frameshift mutation have variable expressivity, leading to different ocular comorbidities and visual outcomes.